Birthplace effect in soccer: a systematic review - Hernández-Simal, L.; Calleja-Gonzalez, J.; Lorenzo Calvo, A.; Aurrekoetxea-Casaus, M. (Journal of Human Kinetics, 2024)
Birthplace is a contextual variable that influences the talent development process of soccer players. The main objective of this systematic review was to compile the scientific literature on the effect of birthplace in soccer. This is the first systematic review to investigate how this contextual factor relates to talent development in soccer. Using the PRISMA methodology, the analysis of the 14 articles that were part of the final review concluded with three main discursive themes: the place of birth and population size, composition of the birthplace and socio-demographic characteristics of the population, and the place of birth and the location of high performance sport centres. This review shows that there are several underlying elements for understanding the effect of the place of birth on the development of talent in soccer. The combination of population density and the level of facilities in the place where the player was born are key in the development of a soccer player. It is not only about the place as a space, but also about what that space means for the development of the player's soccer skills. The findings not only highlight the characteristics of the areas, in terms of density and equipment supply, identified as talent hotspots, but also provide an opportunity to critically reflect on current practices of talent identification and development in soccer.